Normal internal organ weight of Thai adults correlated to body length and body weight - Thamrong Chirachariyavej (2018)
Objective: Examine the relationship between the internal organ weight with body weight and body length. Material and Method: Analysis of data from 250 autopsies from the Ramathibodi Hospital from August 2003 to February 2005. The cases were from sudden unnatural death including accident, homicide and suicide and excluded decomposed bodies, fire related deaths and cases where medical treatment had been given. The age ranged from 15 to 88 years and there were 51 females and 199 males. Parson's correlation coefficient was used to examine the relationship between the internal organ weight with body weight and body length. Results: The mean ± standard deviation (SD) were represented by males and females respectively; Brain 1339 ± 160/1165 ± 184 gm, heart 311 ± 66/278 ± 160 gm, lung 910 ± 347/675 ± 255 gm, liver 1439 ± 365/1214 ± 275 gm, spleen 103 ± 46/92.9 ± 48 gm, kidney 260 ± 68/230 ± 42 gm. Conclusion: The relationship between internal organ weight and body weight showed each internal organ significantly correlated with body weight in males at p-value < 0.05, whereas in females it only correlated to liver, kidney and spleen at p-value < 0.05. For the correlation between internal organ weight and body length, it showed only brain, lung, liver and kidney correlated to the body length in males at p-value < 0.05, but not in females.